MOLECULAR MECHANISM OF GENOTOXICITY OF THE ENVIRONMENTAL POLLUTANT 3-NITROBENZANTHRONE - Stiborova, Marie; Arlt, Volker M.; Henderson, Colin J.; Roland Wolf, C.; Frei, Eva; Schmeiser, Heinz H.; Phillips, David H. (Biomedical papers, 2005)
3-Nitrobenzanthrone (3-NBA) is a suspected human carcinogen identified in diesel exhaust and air pollution. This article reviews the results of our laboratories showing which of the phase I and II enzymes are responsible for 3-NBA genotoxicity, participating in activation of 3-NBA and its human metabolite, 3-aminobenzanthrone (3-ABA), to species generating DNA adducts. Among the phase I enzymes, the most of the activation of 3-NBA in vitro is attributable to cytosolic NAD(P)H:quinone oxidoreductase (NQO1), while N,O-acetyltransferase (NAT), NAT2, followed by NAT1, sulfotransferase (SULT), SULT1A1 and, to a lesser extent, SULT1A2 are the major phase II enzymes activating 3- NBA. To evaluate the importance of hepatic cytosolic enzymes in relation to microsomal NADPH:cytochrome P450 (CYP) oxidoreductase (POR) in the activation of 3-NBA in vivo, we treated hepatic POR-null and wild-type C57BL/6 mice with 3-NBA or 3-ABA. The results indicate that 3-NBA is predominantly activated by cytosolic nitroreductases such as NQO1 rather than microsomal POR. In the case of 3-ABA, CYP1A1/2 enzymes are essential for the oxidative activation of 3-ABA in liver. However, cells in the extrahepatic organs have the metabolic capacity to activate 3-ABA to form DNA adducts, independently from CYP-mediated oxidation in the liver. Peroxidases such as prostaglandin H synthase, lactoperoxidase, myeloperoxidase, abundant in several extrahepatic tissues, generate DNA adducts, which are formed in vivo by 3-ABA or 3-NBA. The results suggest that both CYPs and peroxidases may play an important role in metabolism of 3-ABA to reactive species forming DNA adducts, participating in genotoxicity of this compound and its parental counterpart, 3-NBA.
Keywords: 3-Nitrobenzanthrone/3-Aminobenzanthrone/Cytochrome P450/NAD(P)H:quinone oxidoreductase/Peroxidase/